HYDROMETEOROLOGICAL CONDITION SOVER MUJIB BASIN, JORDAN (Journal of Engineering, 2002)
The (P.E.) values reveal a similar seasonal variation .for six selected climatological stations 6yr)rMujib basin' The average annual values ranges between 2200 mm in the SE region to 1400 mm firrthe NW and SW regions of the basin. The relation between the long-te.- uvirug" values and tl eclimatic parameters (Class A p*, Temperature; Wind, Sun Shine duration % RH %) for thn eclimatological stations were determined using the linear regression equations. High correlatic ncoefficient values suggest that the obtained equations are highly reliable. Mujib basin is divided in, othree climatic zones : Moisture index > -80 where the water balance for this zone show, yy4[r)rsurplus during Dec. to Feb. and water